Door-in-door-out times for patients with large vessel occlusion ischaemic stroke being transferred for endovascular thrombectomy: a Victorian state-wide study. Issue 1 (17th January 2023) - Wong, Joseph Zhi Wen; Dewey, Helen M; Campbell, Bruce C V; Mitchell, Peter J; Parsons, Mark; Phan, Thanh; Chandra, Ronil V; Ma, Henry; Warwick, Alexandra; Brooks, Mark; Thijs, Vincent; Low, Essie; et al.
Abstract : Background: Time to reperfusion is an important predictor of outcome in ischaemic stroke from large vessel occlusion (LVO). For patients requiring endovascular thrombectomy (EVT), the transfer times from peripheral hospitals in metropolitan and regional Victoria, Australia to comprehensive stroke centres (CSCs) have not been studied. Aims: To determine transfer and journey times for patients with LVO stroke being transferred for consideration of EVT. Methods: All patients transferred for consideration of EVT to three Victorian CSCs from January 2017 to December 2018 were included. Travel times were obtained from records matched to Ambulance Victoria and the referring centre via Victorian Stroke Telemedicine or hospital medical records. Metrics of interest included door-in-door-out time (DIDO), inbound journey time and outbound journey time. Results: Data for 455 transferred patients were obtained, of which 395 (86.8%) underwent EVT. The median DIDO was 107 min (IQR 84–145) for metropolitan sites and 132 min (IQR 108–167) for regional sites. At metropolitan referring hospitals, faster DIDO was associated with use of the same ambulance crew to transport between hospitals (75 (63–90) vs 124 (99–156) min, p<0.001) and the administration of thrombolysis prior to transfer (101 (79–133) vs 115 (91–155) min, p<0.001). At regional centres, DIDO was consistently longer when patients were transported by air (160 (127–195) vs 116 (100–144) min, p<0.001). The overall door-to-door time by air was shorter than by road for sites located more than 250 km away from the CSC. Conclusion: Transfer times differ significantly for regional and metropolitan patients. A state-wide database to prospectively collect data on all interhospital transfers for EVT would be helpful for future study of optimal transport mode at regional sites and benchmarking of DIDO across the state.